STRATEGI AKSELERASI DESTINASI EKOWISATA POTRE KONING DI DESA SUMBERCANTING, BONDOWOSO - Hariyadi, Edy; Saputra, Heru S.P.; Maslikatin, Titik; Setyari, Agustina Dewi (PAPUMA: Journal of Community Services, 2024)
This article is about the strategy to accelerate the development of the Potre Koning ecotourism destination in Sumbercanting Village, Wringin District, Bondowoso Regency which has the potential for attractive natural scenery, namely hills, teak and kedawung trees, niches in the form of paddy fields dividing the hills, siring terrace cultivation on the hillsides, waterfall, and Mustajab cave. The preparation stage including initial observation activities, mapping problems in the field, and drafting mentoring activities. Initial observations were carried out to understand the complexity and dynamics that occurred in the field. The data from initial observations was classified based on various problems, obstacles, and shortcomings faced by the Potre Koning ecotourism destination managers. In developing Potre Koning ecotourism, the management needs to pay attention to (1) management by Pokdarwis in managing the ecotourism destination; (2) management of a variety of attractions that can be developed to attract tourists; (3) spatial planning, comfort and ecotourism infrastructure, (4) promotion and marketing through conventional mass media, electronics and social media; (5) security of the ecotourism destination location, and (6) sustainability of the Potre Koning ecotourism destination. Based on the results of service in the field, it was known that the development management factor by Pokdarwis and the role of the village government, Muspika (District Head, Danramil, Kapolsek) were key factors in the success of destination development. Potre Koning ecotourism's development was expected to positively impact local economic growth in Sumbercanting Village, increasing the number of tourists, preserving ecotourism objects, and maximum community participation.